ANALISIS PENGGUNAAN KANSHA HYOUGEN DALAM SERIAL ANIMASI FLYING WITCH KARYA SAKURABI KATSUSHI - Iqbal Maulana; Meira Anggia Putri (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2023)
Kansha hyougen is a symbolic means of showing gratitude or restoring an imbalance caused by the benefits received by the speaker from the hearer. However, many people in Indonesia, especially Japanese language learners, are not fully aware of how important it is to use kansha hyougen when speaking with interlocutors, especially with Japanese individuals. This research aims to describe the variations in the use of kansha hyougen in the anime Flying Witch. The research type is qualitative with a descriptive analysis method, and data collection is done using the observation technique, followed by free observation and note-taking. The data used in this research are utterances containing kansha hyougen from the film Flying Witch. The results of the study found a total of 28 instances of kansha hyougen, which can be categorized into 8 variations: 2 instances of thanking speech acts, 4 expressions of psychological acts of gratitude, 0 instance of expressing gratitude towards an object, 5 instances discussing obligations, 6 instance discussing benefits, 0 offering repayment, 9 instances of positive evaluations, and 2 instances of stating the hearer as the beneficiary.